P Penetapan Kadar Metilparaben Pada Krim Pemutih Wajah Yang Beredar Di Kecamatan Mentaya Hilir Utara Menggunakan HPLC (High Performance Liquid Chromatography) - Sa'diyah, Halimatus; Rahmadani, Rahmadani; Malahayati, Siti (LPPM Universitas Sari Mulia, 2023)
Background: Based on the results of direct observations made by researchers in North Mentaya Hilir District, there are still many traditional markets or cosmetic shops that sell cosmetic products, especially whitening creams that have not been registered with BPOM and do not meet the requirements that have been set, and are indicated to contain methylparabens exceeding the maximum limit set by BPOM. Objective: To analyze the difference in methylparaben levels contained in BPOM registered and non-BPOM registered whitening cream preparations. Methods: Qualitative analysis was carried out by observing retention time, quantitative analysis using HPLC, and making comparisons to see the differences in levels contained in BPOM registered and non-BPOM registered face whitening cream preparations with parametric statistical tests Paired Sample T-Test. Results: The results of the study of BPOM registered and non-BPOM registered whitening creams were positive for containing methylparabens with the average levels contained in BPOM registered whitening cream samples A 0.19 ± 0.003% and samples B 0.79 ± 0.008%. While the levels contained in whitening creams are not registered with BPOM in sample A 0.18 ± 0.0005% and sample B 1.16 ± 0.066%. From the results of determining these levels, there is no difference in methylparaben levels contained. Conclusion: Whitening creams registered with BPOM and not registered with BPOM circulating in North Mentaya Hilir district contain methylparaben.